SUMBANGSIH UJI PROTEIN TELUR DENGAN MENGGUNAKAN BAWANG PUTIH PADA MATA PELAJARAN BIOLOGI MATERI MAKANAN KELAS XI SMA/MA - Syarifah Syarifah; Awalul Fatiqin; Istiroha Istiroha (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2017)
Protein compounds containing amino acids, composed of atoms C, H, O and N. Eggs are thesource of animal protein that has the highest quality or biological value. The purpose of thisstudy was to determine the value of protein in eggs and application in biology subjects. Thisresearch was conducted in June 2016 at IPA Laboratory UIN Raden Fatah Palembang. Proteinanalysis using Kjedahl method. The result of protein analysis obtained was lowest with theaddition of garlic P3 (200 g) the average value of 9.25%, the addition of garlic P2 (150 g) andP1 (100 g) with the mean of 9.42% and 9.48% had the same result systematically. Contributionin biology subjects is given in the method of egg protein test work with the addition of garlic ina systematic manner. In this case it can be concluded Fcount> Ftabel, so the addition of garlicis able to maintain the quality of protein in eggs awake and its contribution in the biology lessonof food in the form LKS.